Correlation between Blood and Cerebrospinal Fluid (CSF) Neutrophil-Lymphocyte Ratio With Bacterial Meningitis Prognosis Patient - Paulus Sugianto; Abdulloh Machin; Devi Ariani Sudibyo; Muhammad Hamdan (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Bacterial Meningitis is a bacterial infection of the central nervous system’s protective membranes called the meninges. Bacterial Meningitis has a high disability and case fatality rate. This inflammatory process not only manifests in CSF but also systemically. The neutrophil-lymphocyte ratio(NLR) can be a predicting factor of severity and prognosis in systemic inflammation. Only a few studies in Indonesia evaluate the neutrophil-lymphocyte ratio as a predictor of mortality in adult bacterial meningitis. This study also aimed to compare neutrophil-lymphocyte ratio in LCS and systemic as a predictor of mortality in patients with adult bacterial meningitis. This is an analytic cross-sectional study in Dr. Soetomo's general hospital—a total sample of 44 bacterial meningitis patients from the inpatient ward of Dr. Soetomo General Hospital Surabaya. The blood Neutrophil- Lymphocyte ratio, Glasgow Coma Scale upon admission, and  Absolute lymphocyte count were significant with bacterial meningitis outcome with p-value less than 0.05. Early detection of bacterial meningitis patient prognosis could alert the healthcare provider to give careful monitoring and aggressive treatment. Abstrak: Meningitis bacterial adalah inflamasi akibat bakteri di selaput otak dan sumsum tulang belakang bernama meningen. Meningitis merupakan penyakit dengan angka kematian dan angka kecacatan yang cukup tinggi walaupun sudah memberikan pengobatan yang tepat. Proses inflamasi ini terjadi tidak hanya pada system saraf pusat namun juga terjadi di seluruh tubuh. Rasio neutrophil-limfosit pada darah selama ini dapat menjadi tanda derajat keparahan dan prognosis pada kasus inflamasi sistemik. Hanya beberapa penelitian yang mencari tentang hubungan rasio limfosit dan neutrophil pada cairan serebrospinal apakah dapat menunjukan derajat keparahan pada infeksi meningitis bakteri. Dalam penelitian ini juga ingin mencari rasio limfosit dan neutrophil darah apakah selaras dengan rasio di dalam cairan serebro spinalis. Penelitian ini merupakan studi reptrospektif kroseksional analitik. Total sampel dari populasi ini adalah 44 yang memenuhi kriteria inklusi dan ekslusi. Secara Statistik didapatkan rasio neutrophil-limfosit darah, tingkat Glassgow Coma Scale saat masuk, dan nilai limfosit absolut signifikan dalam menentukan prognosis pasien dengan meningitis bakteri dewasa (P kurang dari 0.05 ).